(untitled) (Fiep Bulletin - online, 2015)
The prevalence of diabetes is increasing worldwide, becoming the epidemic now as a result, largely, of aging. However, physical inactivity, poor diet and rising obesity rates are also responsible for the global expansion of diabetes. The ergogenic nutritional supplements are those that can promote increased physical performance beyond the physiological capacity and have a thermogenic action in the body. However, the biological activity and scientific validation of these supplements still require studies for its clinical proof as to its thermogenic benefits, thereby casting doubt on the effectiveness of these substances. The objective of this study was to evaluate the effect of supplementation with thermogenic substance, caffeine, on the glycemic levels in type 2 diabetic animals For this 38 Wistar male rats were used, 14 of 24 normoglycemic and diabetic animals were subjected metabolic cage in order to verify the consumption of food and water, urine volume and glucosuria, after that were treated with caffeine and then subjected to biochemical tests. Our results indicate that supplementation with caffeine, a thermogenic often used in physical activities and exercises induces a state of hyperglycemia in diabetic animals and hepatotoxicity. So its prescription and use should be controlled diabetic patients.